Pengaruh Pemberian Pakan Pelet dan Artemia sp. terhadap Kualitas Warna Ikan Badut (Amphiprion ocellaris) - Pandunita, Rai Ayu Ratri Chandra; Julyantoro, Pande Gde Sasmita; Wijayanti, Ni Putu Putri (Current Trends in Aquatic Science, 2023)
This study aims to determine the effect of different feeding on the color quality and growth of clown fish. The feed used in the form of pellets nd Artemia sp. with three treatments and three repetitions. The treatments used were pellet feed (treatment A), Artemia sp feed. (treatment B), and the combination feed of pellet feed and Artemia sp. (treatment C). The research method used is experimental method using Completely Randomized Design (CRD). This research was conducted at PT Agung Aquatic Marine for 1 month October until November. This study used 18 clown fish fed 3 times a day with a dose of 1.5 g of Fengli pellets and 1.5 ml of Artemia sp. for one administration. The parameters measured in this study was color quality parameters. Parameter measurements were carried out once a week. The media used was a aquarium with a volume of 2500 ml with a size of 40 × 30 cm. Color quality parameters are measured with a color chart paper base called M-TCF and then ranking according to the numbers on the paper. The results of this study showed that the quality of the body color of clown fish fed pellet feed, Artemia sp. feed, and combination feed faded. Based on the results of the research that was tested by ANOVA analysis, it can be concluded that this different feeding had no significant effect (P>0.05) on the color quality of clown fish.